Promoting lifestyle medicine research in Ghana: lessons learned from Centre for Lifestyle Medicine and Behaviour (CLiMB) Ghana hybrid workshop - Osei-Kwasi, Hibbah; Boateng, Daniel; Zakariah-Akoto, Sawudatu; Ojwang, Alice; Agbozo, Faith; Assasie, Emmanuel; Addo, Phyllis; Blay Adjei, Maame Yaakwaah; Mogre, Victor; Akparibo, Robert; Aryeetey, Richmond; Levy, Andrew; et al. (Frontiers in Public Health, 2025)
The rapid rise in urbanization across many African countries is contributing to the increasing prevalence of non-communicable diseases (NCDs) in both adults and children and presents a significant challenge to health services across the continent. In May 2023, a 2-day workshop was held in Ghana, coordinated by the Centre for Lifestyle Medicine and Behaviour (CLiMB) at Loughborough University and in collaboration with partners from three Ghanaian Universities. The workshop brought together academics, clinicians, public health specialists and civil society organizations from Ghana, UK, France, the Netherlands, the USA, and Kenya. Our main objective was to identify scalable lifestyle interventions to address the growing burden of NCDs in Ghana. The 2-day workshop focused on identifying salient research priorities for the prevention of NCDs. The immediate research priorities outlined were (1) conduct observational research in Ghana to identify feasible dietary and physical activity changes to reduce NCDs; (2) undertake a Delphi Study to -prioritize a research agenda on NCDs, focusing on lifestyle behaviors and involving researchers, policymakers, and implementers; (3) perform a comprehensive mapping and realist synthesis of diet and physical activity interventions, policies, and programs in Ghana and across Africa to assess their effectiveness and relevance; and (4) evaluate contextual factors influencing physical activity participation in the regions of Ghana and Kenya. Workshop participants highlighted the importance of adopting a multidisciplinary research approach and emphasized the critical need for strong collaboration among all stakeholders, including the public, for implementing effective lifestyle interventions to improve the health of Ghanaians.